Amide proton transfer (APT) contrast for imaging of brain tumors - Zhou, Jinyuan; Lal, Bachchu; Wilson, David A.; Laterra, John; van Zijl, Peter C.M. (Magnetic resonance in medicine, 2003)
In this work we demonstrate that specific MR image contrast can be produced in the water signal that reflects endogenous cellular protein and peptide content in intracranial rat 9L gliosarcomas. Although the concentration of these mobile proteins and peptides is only in the millimolar range, a detection sensitivity of several percent on the water signal (molar concentration) was achieved. This was accomplished with detection sensitivity enhancement by selective radiofrequency (RF) labeling of the amide protons, and by utilizing the effective transfer of this label to water via hydrogen exchange. Brain tumors were also assessed by conventional T1‐weighted, T2‐weighted, and diffusion‐weighted imaging. Whereas these commonly‐used approaches yielded heterogeneous images, the new amide proton transfer (APT) technique showed a single well‐defined region of hyperintensity that was assigned to brain tumor tissue. Magn Reson Med 50:1120–1126, 2003. © 2003 Wiley‐Liss, Inc.